Capacitación científica y actividades de la red. Perú - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
The CIAT regional project in Peru has given max. priority to the improvement of bean var. Substantial progress was made in developing var. resistant to BCMV and rust (CIFAC 1277 and CIFAC 1288), with good adaptation in the Valle de Chincha. Another significant advance was the establishment of the 1st network expt.: the uniform yield trial for climbing and bush beans for the Sierra/1985. In both trials the best advanced lines were included in the regional programs of Cuzco and Cajamarca. To date, 6 lines (A 59, San Cristobal 83, BAT 1393, G 4523, V 8025, and G 4495) have been selected for their good adaptation and yields under drought conditions. In the Valle de Chincha, 5 lines (G 6278, G 2587, G 3736, A 211, and FR 2811) were selected for their resistance to nematodes (Meloidogyne sp.). (CIAT)